(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Electrical engineering is subdivided in to a wide range of subfields including, electronics, digital computers, telecommunications, control systems, signal processing and microelectronics. In this paper author is trying to review, different methodologies available for control the speed of an induction motor by using three level diode clamped multilevel inverter. With the help of V/f method an open loop speed control can be achieved. The main objective of this paper is to carry a systematic review of the available literature and to control the speed of induction motor techniques.